IMPROVEMENT OF METHODS OF IDENTIFICATION OF MEAT TYPES - Приліпко, Тетяна; Косташ, В.Б.; Підлісний, В.В.; Семенов, О.М (Modern engineering and innovative technologies, 2023)
It was established that it is practically impossible to control all indicators of meat quality, and it has no meaning from the point of view of the requirements of specific market segments, as well as from the point of view of ensuring the efficiency of b